Analysis of sequence variants in the 3’UTR of CDKN2A gene in melanoma patients - Przybyła, Anna; Lamperska, Katarzyna; Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2015)
Background : The 3’UTR region plays a crucial role in regulating gene expression at posttranscriptional levels. Any changes in sequence in this region can cause numerous pathologies and can also lead to tumour development. The most common changes reported in in the CDKN2A gene are the 148Ala/Thr in exon 2 and 500C>G and 540C>T in the 3’UTR region. They are suspected of having a great impact on cancer progression. Since the role of these sequence variants in the Polish population in the development of melanoma has not been confirmed, the importance of 3’UTR polymorphisms in the regulation of gene expression was tested. Material and methods : First, genetic analysis in a group of 285 melanoma patients was performed and the obtained results were correlated with the clinical course of melanoma. Then vectors carrying 3’UTR sequence variants were prepared and the level expression of the reported gene was measured. Results : Within this study no correlation between the presence of 148Ala/Thr polymorphism and cancer in the family was observed. There was a correlation between the presence of this polymorphism and breast cancer and melanoma in the same patient. There was no correlation between 500C>G polymorphism and tumour localisation, age of diagnosis, and type of cancer in patients’ family, but a correlation between the percentage of patients dying and the 500C>G variant was observed. Conclusion : The results of functional tests indicated that the presence of polymorphism in the 3’UTR region of the CDKN2A gene resulted in changes in the level of reporter gene expression.